Equity valuation: Unilever Indonesia - Evantha, Raynaldo (2021)
Unilever Indonesia specializes in the manufacture and sale of fast-moving consumer products in the areas of nutrition, hygiene and personal care. It operates in four segments, including personal care, food, beverage and home care. The Company has maintained a sustainable growth in stock price over the years since its Initial Public Offering (IPO) in 1982. At the end of 2020, the Company was the 3rd largest on stock-market capitalization in Indonesia Stock Exchange standing at USD 21.4 billion. The present project aims at carrying out Unilever Indonesia's firm valuation study, using the Discounted Cash Flow approach to achieve the fair value for each share on December 31st, 2020. The key results show that the shares of Unilever Indonesia are valued slightly above their fair value.